PENERAPAN STANDARD OPERATING PROCEDURE MAKE UP OCCUPIED DIRTY ROOM DI HOTEL PANGERAN BEACH PADANG - Ghurfah, Yahdi Al; Yuliana, Yuliana; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to describe the implementation of standard operatingprocedures make up occupied dirty room at Hotel Pangeran Beach Padang wereevaluated from eight indicators namely: Access to the room, the first step whenyou are in the room, stripping, making beds, dusting, cleaning the bathroom,vacuum carpet and recheking. This type of research is descriptive with qualitativedata. Data collection techniques performed by using the method of observation,interviews, and documentation. The results showed that the application ofstandard operating procedures make up occupied dirty room at Hotel PangeranBeach Padang is generally not good, because there are several indicators that didnot applied correctly by all roomboy. On indicators dusting, cleaning thebathroom and vacuum the carpet all roomboy not apply SOP correctly. Whileother indicators have been applied correctly by four of the eight people roomboy.Keyword: Application of SOP, Make Up Occupied Dirty Room